Taxonomic revision of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae): an integrative proposal to delimit species using a multidisciplinary strategy - Motta, Veronica de Barros Slobodian (2018)
Primary taxonomic research in neotropical ichthyology still suffers from limited integration between morphological and molecular tools, despite major recent advancements in both fields. Such tools, if used in an integrative manner, could help in solving long-standing taxonomic problems. The genus Pimelodella Eigenmann & Eigenmann, 1888 is a perfect case for an integrative and multidisciplinary approach in taxonomy. Pimelodella is a genus of the Heptapteridae broadly distributed throughout trans- and cis-Andean South America, and one of the main components of Neotropical Ichthyofauna. Nowadays is the most species-rich genus of the family, with 79 valid species. However, the validity and delimitation of those species is extremely problematic, due their broad geographic distribution, conserved morphology, and ancient and imprecise descriptions. Pimelodella is undoubtedly one of the most severe taxonomic bottlenecks in neotropical ichthyology. This project presents a taxonomic revision of Pimelodella using an integrative morphological-molecular approach. The traditional taxonomic revision covers the genus in its entirety, with all the components of this kind of study. All types were examined, and the number of valid species herein recognized was reduced to 55 species, for which full descriptions are presented. The molecular taxonomy was done for a circumscribed subset of the genus, with representation enough to understand the molecular divergences and compare them with the traditional taxonomy results, allowing an evaluation of the results of the revision.